MOTIVASI DAN PERSEPSI WISATAWAN MANCANEGARA BERWISATA ALAM TREKKING MOUNTAIN DI TAMAN WISATA ALAM GUNUNG BATUR BUKIT PAYANG - Witarsana, I Kadek; Leli Kusuma Dewi, Luh Gede; Susrami Dewi, Ni Gusti Ayu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 1 (2017): Jurnal IPTA (July 2017), 2017)
Trekking mountain as one of foreign tourism activities in Mount Batur became more popular now days. The beauty of the sunrise from the top of the mountain become an attraction for foreign tourists to conduct trekking mountain in the Natural Tourism Park of Mount Batur Hill Payang. Therefore, the purpose of this study was to determine the motivation and perception of foreign tourists to do trekking mountain in the Natural Tourism Park of Mount Batur Hill Payang. This study using purposive sampling by distributing questionnaires to 150 foreign tourists as respondents. Some techniques were used such as: observation, interview, questionnaire, literature, and documentation. And for data analysis used qualitative and quantitative analysis. The results of this study showed that motivation of push factor affects tourists do trekking in Mount Batur are to see the sights at the top of the mountain in order to feel relaxed, to get a different atmosphere, and doing something new and different. While the motivation of pull factor that attracts tourists for trekking mountain Batur are the stunning natural environment, the presence of wildlife, as well as the atmosphere and climate of Mount Batur. Perception rating indicates that the services provided by trekking guide has been very good, but the rating was less about the cleanliness of the toilets and track trekking in the Natural Tourism Park of Mount Batur Hill Payang.